Second Person: role-playing and story in games and playable media - Cobo-Durán, Sergio (COMUNICACIÓN. Revista Internacional de Comunicación Audiovisual, Publicidad y Estudios Culturales, 2022)
Second Person: role-playing and story in games and playable media. Pat Harrigan y Noah Wardrip-Fruin Cambridge, Massachusetts, MIT Press, 2007 408 páginas.